Effect of Incorporating Beetroot on Shelf-Life Stability of Functional Pickles - Hossain, B; H, Shameem; Tanny, UH; Apou, AC; Sohag, MR (International Journal of Membrane Science and Technology, 2023)
Beetroot pickles are a relatively new vegetable gaining market share in Bangladesh. It is a naturally growing root vegetable known for its health benefits due to its phytochemicals and bioactive compounds. Beetroot (beta vagaries) has been shown to improve clinical and physiological conditions and promotes good health. And has become a potential functional food that can prevent disease. One of its compounds, bataline, has shown chemo preventive, sedative, and disease-preventive activity. There is a fundamental difference between the newly developed pickled beet sample and the commercial one. The sample developed was 11.50 Brix, 55.5 mg (%) Vitamin C, 27.5% Moisture, 3.25% Dietary Fiber, 37.3 % Carbohydrate, 1.25% Protein, 2.7% Ash, 28%, 195 mg (%) Bataline, pH 4. Microbiological analysis of samples after 270 days showed 5/g colony forming units (cfu), with an overall acceptance of 70% among trained panelists after 270 days of storage. Vitamin C and added salt prevent oxidative degradation and extend the shelf life of pickled beets.